Protocol for the Trial to Establish a Causal Linkage Between Mycotoxin Exposure and Child Stunting: A Cluster Randomized Trial. (7th June 2021) - Phillips, Erica; Ngure, Francis; Smith, Laura; Makule, Edna; Turner, Paul; Nelson, Rebecca; Kimanya, Martin; Stoltzfus, Rebecca; Kassim, Neema
Abstract: Objectives: The objective of this community-based cluster randomized trial is to measure the effect of a reduced aflatoxin diet fed between 6–18 months on length-for-age Z scores at 18 months. Methods: All 52 health facilities in the Kongwa District of Central Tanzania were randomized into the control or intervention arm. Mothers who bring their infants to Expanded Program on Immunization (EPI) visits are recruited through these facilities when the infants are between 1.5–3 months of age. Starting at 6 months of age mothers in the intervention arm receive a low-aflatoxin pre-blended porridge flour containing maize and groundnut (ratio 4:1 respectively) and low-aflatoxin groundnut flour, whereas the same porridge mix and groundnut flour are promoted through education but acquired by the household in the control arm. Both arms receive the same infant and young child feeding education and a thermos flask. A total of 3120 infants will be recruited into the study over one year. Data will be collected at four time points – at recruitment and when the infants are 6, 12 and 18 months of age. In a cohort of 600 infants, additional data will be collected at 9 and 15 months of age. The primary outcome is length-for-age Z scores at 18 months. Secondary outcomes include Z scores for weight-for-age, middle upper arm circumference and head circumference, and the blood biomarker aflatoxin-albumin in the full sample, with the urine biomarker aflatoxin M1 analyzed in the cohort only. Results: This is a study protocol. No results are included here. Conclusions: Better understanding the etiology of childhood stunting can lead to more appropriate interventions and policies to further reduce linear growth faltering. Funding Sources: The Bill and Melinda Gates Foundation.